Association Between Fatigue and Cognitive Impairment at 6 Months in Patients With Ischemic Stroke Treated With Acute Revascularization Therapy - Graber, Mathilde; Garnier, Lucie; Duloquin, Gauthier; Mohr, Sophie; Guillemin, Sophie; Ramaget, Océane; Piver, Ariane; Tainturier, Cécile; Bret-Legrand, Christine; Delpont, Benoit; Blanc-Labarre, Christelle; Guéniat, Julien; et al. (Frontiers in Neurology, 2019)
Background: Fatigue is a frequent symptom after stroke. We aimed to determine the association between fatigue and cognitive performance in patients with ischemic stroke who received acute revascularization therapy (IV thrombolysis and/or mechanical thrombectomy). Methods: Seventy patients were prospectively included in the stroke unit of the University Hospital of Dijon, France. A follow-up was performed at 6 months with clinical examination, fatigue assessment by the Fatigue Severity Scale (FSS), and a comprehensive neuropsychological evaluation. Patients with fatigue (FSS score > 4) were compared with patients without fatigue. Neuropsychological factors associated with fatigue at 6 months were analyzed using multivariable logistic regression models. Results: Fatigue was reported by 34.3% of patients. Patients with fatigue were older, had more frequent residual handicap, depressive symptoms, and impaired quality of life. They had more frequently low score (<26) on the MoCA scale (79.2% versus 47.8%, OR=4.15; 95% CI: 1.32-13, p= 0.015), memory impairment (60% versus 30.6%, OR=3.41; 95% CI: 1.09-10.7, p=0.035), and executive dysfunction (65% versus 30.8%, OR=4.18; 95% CI: 1.33-13.1, p=0.014). In multivariable logistic regression analysis, only memory impairment was independently associated with fatigue (OR=5.70; 95% CI: 1.09-29.6, p=0.039). Further analyses restricted to non-depressed patients (n=58, 84.1%) showed in multivariable models that a score < 26 on MoCA scale (OR 5.12; 95% CI: 1.00-26.2, p=0.05), and a memory impairment (OR=6.17; 95% CI: 1.06-35.9, p=0.043) were associated with fatigue. There was also a non-significant trend towards an association between divided attention deficit and fatigue (OR=6.79; 95% CI: 0.80-57.6, p=0.079). Conclusion: The association between fatigue and subtle cognitive impairment including memory or attention deficits could be of interest in elaborating future interventional studies to evaluate the impact of therapeutic strategies, including cognitive rehabilitation, on fatigue.